Penafsiran Ayat-Ayat tentang Birrul Walidain - Aulia Khairunnisa Siregar; Siti Nur Aisyah (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
Birrul Walidain is a concept in Islam that emphasizes the importance of filial piety and treating parents well. This term comes from the words "birr" which means goodness and "walidain" which means parents. This concept is an integral part of Islamic teachings and has broad implications in everyday life. In the Al-Qur'an, Allah SWT commands Muslims to be filial to their parents, as stated in Surah Al-Isra' verses 23-24. This verse emphasizes the importance of treating parents well, not disobeying them, and always praying for them. In everyday life, Birrul Walidain can be realized by obeying parents' orders, treating them with courtesy and respect, and always praying for them. In this way, Muslims can gain the approval of Allah SWT and strengthen their relationship with their parents.